SISTEM MONITORING PENDINGINAN BUAH MANGGA DARI SISI TEMPERATUR DAN KELEMBABAN BERBASIS IOT - Westari, Dwianti; Fitriyanto, Indra; Karsid, Karsid; Khoerun, Bobi; Ariska, Afid (P3M Politeknik Negeri Indramayu, 2025)
The mango cooling monitoring system based on the Internet of Things (IoT) is developed to maintain quality and freshness during storage. This study utilizes the ESP32 module as the central processing unit, integrated with DHT22 temperature and humidity sensors, enabling real-time monitoring. The collected data is transmitted to an IoT platform for remote monitoring. Testing results indicate that the system accurately monitors storage conditions with minimal error rates. The implementation of IoT technolody enhances user convenience, improves storage efficiency, and reduce product loss due to improres handling. This research is expected to contribute to the advancement of agricultural technology and the optimization of agricultural product distribution.